Kajian Penggunaan Antibiotik Pada Penyakit Demam Tifoid di Ruang Rawat Inap Anak RSUD dr. Soekardjo Tasikmalaya 2015 - Nuri Handayani (STIKes Persada Husada Indonesia, 2017)
Typhoid fever is one of the emerging infectious diseases in the globalization era, which is caused by health problems and bad sanitation. The treatment of typhoid fever needs antibiotics. There are some problems with the usage of antibiotics, which is causing the emergence of resistants. The pattern of antibiotic usage is needed to minimize resistant occurrence in the treatment of typhoid fever. The purpose of this study is to describe the pattern of antibiotic usage in pediatric patients with typhoid fever in the children ward of RSUD dr. Soekardjo Tasikmalaya in 2015. This study uses descriptive and retrospective method. Data is taken from patient’s medical record, and analyzed with descriptive statistic. The results showed the most widely used antibiotics for therapy of typhoid fever in children in RSUD dr. Soekardjo Tasikmalaya is ceftriaxone (55.54%). The use of a combination of antibiotics is 8.62%. Change of antibiotic therapy based on length of therapy is not compatible (12.07%).